(untitled) (Agro Productividad, 2025)
Objective: To evaluate the effect of the application of commercial sargassum extract as foliar biofertilizer in sugarcane cultivation. Design/methodology/approach: Five fertilization treatments were applied in an experimental plot cultivated with sugarcane: Conventional mineral fertilization (T1); Foliar fertilization with 100% sargassum extract (T2); Foliar fertilization with 50% sargassum extract (T3); Conventional mineral fertilization at 50% plus foliar fertilization with 50% sargassum extract (T4); and control without fertilization (T5), in a completely randomized experimental design. Results: The greatest stem height was observed in the statistically equal treatments T1, T2 and T4, but higher than that of the control. The longest diameter was observed in the T4 treatment, significantly higher than that of the control, in which a statistically lower number of leaves was also observed. The highest field yield was observed in statistically identical treatments T1, T2 and T4, but higher than that found in the control treatment. Limitations on study/implications: Further evaluation of commercial sargassum extracts applied as foliar fertilizers in crops is considered necessary to corroborate the results presented here. A study of the action mechanisms of the compounds found in sargassum extract on crop physiology, when applied as foliar fertilizers, is also considered necessary. Findings/conclusions: Commercial sargassum extract is a sustainable alternative for sugarcane biofertilization, which does not pose a risk of chemical contamination like that of conventional mineral fertilization.